Characterizing restricted and unusual interests in autistic youth. Issue 2 (1st December 2022) - Spackman, Emily; Smillie, Luke D.; Frazier, Thomas W.; Hardan, Antonio Y.; Alvares, Gail A.; Whitehouse, Andrew; Uljarević, Mirko
Abstract: A broad range of interests characterized by unusual content and/or intensity, labeled as circumscribed interests (CI), are a core diagnostic feature of autism. Recent evidence suggests that a distinction can be drawn between interests that, although characterized by unusually high intensity and/or inflexibility, are otherwise common in terms of their content (e.g., an interest in movies or animals), labeled as restricted interests (RI), and interests that are generally not salient outside of autism (e.g., an interest in traffic lights or categorization), labeled as unusual interests (UI). The current study aimed to further characterize RI and UI by exploring their association with age, sex, IQ, and social motivation, as well as to examine differences in the adaptive benefits and negative impacts of these two subdomains. Parents of 1892 autistic children and adolescents ( M age = 10.82, SD age = 4.14; 420 females) completed an online survey including the Dimensional Assessment of Restricted and Repetitive Behaviors and the Social Communication Questionnaire. Both RI and UI were found to be highly frequent. Sex‐based differences were observed in the content, but not intensity, of CI such that females were more likely to show interests with a social component. Finally, RI and UI showed distinct patterns of association with age, sex, IQ, and social motivation, as well as metrics of adaptive benefits and negative impacts. Findings afford a more nuanced understanding of sex‐based differences in CI and, crucially, provide preliminary evidence that RI and UI represent distinct constructs that should be studied independently in future research. Lay Summary: Autistic individuals may present with a range of different special interests. In this paper, we show that different types of interests have different patterns of association with age, IQ, sex, and social motivation and argue that it is important for future research to use more specific and comprehensive measures of special interests.